KECEMASAN MATEMATIKA DAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SEKOLAH MENENGAH PERTAMA - Faiq Zulfikar Hadi; Maman Fathurrohman; Cecep Anwar Hadi (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
This research is conducted by the low mathematics critical thinking ability of students in junior high schools, especially in VII grade .Students of VII grade commonly are transitioning from elementary school to junior high school could be a reason how low students of VII grade on mathematic critical thingking ability. The low ability mathematics critical thingking one of caused by mathematics anxiety. This study aims to find a relationship between math anxiety and mathematics critical thinking ability of VII grade at SMPN 5 Serang City. The method of this research is quantitative descriptive by making 110 students from VII grade as a sample. The data were collected using questionnaire and test. The result of this study indicate that 1) the ammount of correlation between math anxiety with critical thingking ability is -0,5991> rs table 0,1695, which means there is a significant and negative relationship between anxiety and critical thingking ability 2) the average of students’s mathematics critical thingking ability is different where score between students with low anxiety have a better score than student with mid anxiety and low anxiety,and students with mid anxiety have a better score than students with high anxiety, and students with mid anxiety have a better score than students with high anxiety.